2020
DOI: 10.1111/ejn.14747
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical mechanisms governing large‐scale brain network dynamics underlying individual‐specific variability of perception

Abstract: Perception necessitates interaction among neuronal ensembles, the dynamics of which can be conceptualized as the emergent behavior of coupled dynamical systems. Here, we propose a detailed neurobiologically realistic model that captures the neural mechanisms of inter-individual variability observed in cross-modal speech perception. From raw EEG signals recorded from human participants when they were presented with speech vocalizations of McGurk-incongruent and congruent audiovisual (AV) stimuli, we computed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 78 publications
1
21
1
Order By: Relevance
“…The EEG data further revealed an event-related potential (ERP), phase-locked to the flicker, fluctuating at 10 Hz, suggesting an increase in the certainty about the physical time-dimension in the neural circuits of the brain, which can be analyzed as mutual information. Authors also found desynchronization of spontaneous neural oscillations during the flicker observation period, which is consistent with the presence of desynchronization during information processing (Kumar et al, 2020 ). Furthermore, during time reproduction, there was an increase of the spontaneous alpha oscillation amplitude.…”
Section: Contributionssupporting
confidence: 74%
“…The EEG data further revealed an event-related potential (ERP), phase-locked to the flicker, fluctuating at 10 Hz, suggesting an increase in the certainty about the physical time-dimension in the neural circuits of the brain, which can be analyzed as mutual information. Authors also found desynchronization of spontaneous neural oscillations during the flicker observation period, which is consistent with the presence of desynchronization during information processing (Kumar et al, 2020 ). Furthermore, during time reproduction, there was an increase of the spontaneous alpha oscillation amplitude.…”
Section: Contributionssupporting
confidence: 74%
“…In recent work using EEG- and fMRI-based neuroimaging evidence, it was found in healthy young individuals that the time differences of cross-modal perception may particularly tax multisensory processing and temporal dichotomy of dual-stream processing (streams for action versus stimulus awareness), in which local sensory stimuli must be integrated from two modalities (audio and visual, for example). In particular during dynamic perception, the sensory signals are built up and integrated over time (Kumar et al, 2016 ; Kumar, Dutta, Talwar, Roy, & Banerjee, 2012 ; Ray et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported variability among participants perceiving the McGurk illusion. This variability arises because some participants experience the McGurk illusion more frequently than others (MMK Benoit et al ., 2010; Nath & Beuchamp, 2012; Strand JF et al ., 2014; Mallick et al ., 2015; Kumar et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%